Numerical Simulation of Hybrid FRP-Concrete-Steel Double-Skin Tubular Columns under Close-Range Blast Loading - Wang, W.; Wu, C.; Li, Jun (American Society of Civil Engineers, 2018)
Hybrid fiber-reinforced polymer (FRP)-concrete-steel double-skin tubular columns (DSTCs) are a new form of composite columns that consist of an outer FRP tube and an inner steel tube, with the space between them filled with concrete. Although many studies have been conducted on the hybrid DSTCs, no studies have been conducted on their behavior under blast loading. This study presents the results of a numerical study on the behavior of hybrid DSTCs under close-in blast loading. Numerical models of hybrid DSTCs are developed using finite-element code LS-DYNA, and the reliability of the developed models are validated with available testing results. With the validated models, numerical simulations are carried out to investigate the structural responses of hybrid DSTCs under blast loading. The simulation results indicate that the hybrid DSTCs behave in a ductile manner under blast loading. The outer FRP tube can effectively provide confinement to the infilled concrete, and the inner steel tube plays a key role in resisting the blast loading. Detailed parametric analyses are conducted to investigate the influences of different parameters on the blast behavior of hybrid DSTCs. The blast resistance capacities of the hybrid DSTCs, concrete-filled steel tubes (CFSTs), and concrete-filled double-skin steel tubes (CFDSTs) are compared and discussed based on the simulation results.